Saamen skandinaavisten lainasanojen tutkimuksen tilasta ja näkymistä - Markus Juutinen; Juha Kuokkala (2023)
A presentation on Scandinavian/Norse loanwords in Saami, particularly on their dating criteria and the determining of the source form.